Evaluation of Drug Blood-Brain-Barrier Permeability Using a Microfluidic Chip - Jung Yoon Yang; Dae-Seop Shin; Moonkyu Jeong; Seong Soon Kim; Ha Neul Jeong; Byung Hoi Lee; Kyu-Seok Hwang; Yuji Son; Hyeon-Cheol Jeong; Chi-Hoon Choi; Kyeong-Ryoon Lee; Myung Ae Bae (MDPI AG, 2024)
The blood-brain-barrier (BBB) is made up of blood vessels whose permeability enables the passage of some compounds. A predictive model of BBB permeability is important in the early stages of drug development. The predicted BBB permeabilities of drugs have been confirmed using a variety of in vitro methods to reduce the quantities of drug candidates needed in preclinical and clinical trials. Most prior studies have relied on animal or cell-culture models, which do not fully recapitulate the human BBB. The development of microfluidic models of human-derived BBB cells could address this issue. We analyzed a model for predicting BBB permeability using the Emulate BBB-on-a-chip machine. Ten compounds were evaluated, and their permeabilities were estimated. Our study demonstrated that the permeability trends of ten compounds in our microfluidic-based system resembled those observed in previous animal and cell-based experiments. Furthermore, we established a general correlation between the partition coefficient (<semantics>Kp</semantics>) and the apparent permeability (<semantics>Papp</semantics>). In conclusion, we introduced a new paradigm for predicting BBB permeability using microfluidic-based systems.